2022
DOI: 10.1016/j.hrtlng.2022.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory rehabilitation in patients recovering from severe acute respiratory syndrome: A systematic review and meta-analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…The need for rehabilitation during and after the Covid-19 pandemic has been noted by many authors (Gutenbrunner et al, 2020;Agostini et al, 2021;Barman et al, 2022;Ceravolo et al, 2020;Halpin et al, 2021).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The need for rehabilitation during and after the Covid-19 pandemic has been noted by many authors (Gutenbrunner et al, 2020;Agostini et al, 2021;Barman et al, 2022;Ceravolo et al, 2020;Halpin et al, 2021).…”
Section: Discussionmentioning
confidence: 96%
“…The examiner should be trained in cardio-pulmonary resuscitation, and the room should be equipped with oxygen and an emergency kit. Typically, during the test, maximum loads and a variety of scales and tools are used (Mancini et al, 2021;Barman et al, 2022). The patient determines dyspnea and fatigue himself, so it is a subjective assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid recovery and improvement reflects the effect of regular physical therapy. Barman et al showed improvement of lung function in COVID patients receiving respiratory rehabilitation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory rehabilitation improves symptoms of dyspnoea, relieves anxiety, reduces complications, minimises disability, preserves function, and improves the quality of life both in the acute phase and after discharge. [2][3][4] Telerehabilitation is the provision of rehabilitation services through telecommunication networks or the internet offering remote treatments to the people in their homes or from a distance. 5 6 Since COVID-19 emerged and caused a huge burden on the health system, many patients are not able to receive their face-to-face treatments and also people with chronic or longstanding health conditions are unable to continue their follow-up as usual and professionals cannot attend all of the consultations.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 has clinical manifestations of cough, shortness of breath, chest pain, fatigue and severe viral pneumonia with respiratory failure and/or death. Respiratory rehabilitation improves symptoms of dyspnoea, relieves anxiety, reduces complications, minimises disability, preserves function, and improves the quality of life both in the acute phase and after discharge 2–4. Telerehabilitation is the provision of rehabilitation services through telecommunication networks or the internet offering remote treatments to the people in their homes or from a distance 5 6.…”
Section: Introductionmentioning
confidence: 99%